Initial Cytotoxicity of Mineral Trioxide Aggregate (MTA) during Setting on Human Mesenchymal Stem Cells - Soo-Youn Kim; Su-Min Lee; Jung-Hwan Lee (Advances in Materials Science and Engineering)
Bone-marrow-derived human mesenchymal stem cells (hMSCs) which are important cell source for hard tissue regeneration stay near periapical lesions of tooth, playing an essential role in periodontal regeneration. Since the biomineralization process of MSCs is largely governed by the initial local environment, it is crucial to know the biological effects of dental bioceramic (mineral trioxide aggregate (MTA)) right after implantation. The purpose of this study was to evaluate the initial cytotoxicity of 4 different commercially available MTA materials (Endocem MTA, Ortho MTA, ProRoot MTA, and MTA Angelus) against hMSCs during or after setting using extracts of materials. The materials were mixed separately and placed into disk-shaped Teflon split molds (10 mm diameter and 2 mm thickness), and the sample discs were separated and eluted in the culture medium for 24 h. The extracts were exposed to hMSCs, and cytotoxicity was evaluated by the WST assay. In the present study, all 4 MTA products tested showed severe cytotoxicity at 100% and 50% extract, while 25% and 12.5% revealed 30∼100% depending on the MTA products. Endocem MTA showed severe cytotoxicity at 12.5% extract, while others showed relatively higher cell viability compared to Endocem MTA. Images of live and dead cells represented less live cells at 25% and 12.5%, confirming cell viability assay. Therefore, careful consideration of the concentration of MTA extracts is necessary, especially when applying MTA to the elderly patients to maintain the viability of hMSCs.